MOTIVASI MASYARAKAT DALAM MENGELOLA HUTAN RAKYAT DI DESA NGLANGGERAN, KECAMATAN PATUK, KABUPATEN GUNUNG KIDUL, DAERAH ISTIMEWA YOGYAKARTA - , MARZIAN BENAZIR S ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Community forest is one form of natural resources management based on community initiatives. The development of community forest is done byowned society land. The kind of plant planted is wood and agriculture which can be used for society itself or sold for increasing income. Community forest management takes important roles on fulfilling needs of Nglanggeran villagers. This research is aimed on knowing the history of community forest management, society motivation on managing community forest and the influence of motivation in the action of Nglanggeran villagers on managing community forest. The research was conducted in Nglanggeran Village, Patuk Region, GunungKidul Regency, Yogyakarta Special Region. This research used qualitative approach with phenomenology method. Data collection is done by location observation, deeply interview using interview guide and documentation study. Then, the analysis method of qualitative data based on Miles and Huberman (1984) is used on data analyzing. Based on the research result, known that the history of forest community in Nglanggeran Village has been developing which is parted into four periods. They are before 1960, 1961-1973, 1974-1993 and 1993 Forming Joint Farm Group in 2007 until wood certifications was done in 2013. Nglanggeran villagers face forest as a place for earning with planting. Society motivation managing community forest is a motivation for maintaining life, safe, caring and loving, and also self-regard. Motivation is a psychiatric phenomenon pushing human to do what they want to achieve. Strong motivation in Nglanggeran villagers on managing community forest ignites efforts for achieving aims and hopes until satisfaction has been reached.